Telaah Kritis Atas Kompetensi Toleran dalam Kurikulum Program Keagamaan Madrsah Aliyah - Abu Amar (PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2021)
This study applies a descriptive qualitative comparative method based on literature data, with the aim of exploring tolerant competence in Pendidikan Agama Islam (PAI) subjects in the Madrasah Aliyah Program Keagamaan as in KMA 165/2014 and KMA 183/2019. Content analysis is used to analyze the content of tolerance in the formulation of the basic competencies of Islamic religious education and to emphasize the development, differences and similarities in the formulation of tolerant competencies. Tolerant competence in KMA 165 of 2014 has not been used as a basis for curriculum development, on the contrary in KMA 183/2019 it has become the basis of curriculum development. The formulation of tolerant basic competence (KD) developed from KI-2 is more dominant than KD developed from KI-1, KI-3 and KI-4. The basic tolerant competence in Islamic religious subjects with religious specialization in the two curricula have proportional similarities both in number and formulation. In KMA 165/2014 tolerant competence is universally Islamic, while in KMA 183/2019 it still does not eliminate the universality of Islam by emphasizing tolerance within the framework of the nationalism of the Unitary State of the Republic of Indonesia. In terms of the object of developing the study material for the verses of the Qur'an on tolerance there is no change at all, while from the study of Hadith there is one addition.